STRENGTHENING THE NATIONAL MANAGEMENT INFORMATION SYSTEM (SIMNAS) IN SUPPORTING THE ACCELERATION OF INDONESIAN NATIONAL DEVELOPMENT - Fitry Taufiq Sahary; K.P.Suharyono Soemarwoto Hadiningrat (Yayasan Inspirasi Merah Putih Indonesia, 2024)
The National Management Information System (Simnas) to support the acceleration of national development in Indonesia is important and urgent, especially in the digital era where the transformation carried out has not achieved the expected results; as a result of various factors both domestic and foreign. Obstacles and challenges are very dynamic. The current condition of Simnas is inadequate in relation to ideal hopes for the future, where electricity and internet network infrastructure support cannot yet be enjoyed by the entire population. This research design is descriptive to describe the phenomenon of the research variables, namely strengthening the National Management Information System and accelerating Indonesia's national development; with a national resilience approach which aims to find and describe obstacles and challenges in strengthening the National Management Information System (Simnas) to support the acceleration of national development; and efforts to overcome them. The method used in this research is a qualitative descriptive method to describe the phenomenon of the research variables, namely strengthening the National Management Information System and accelerating Indonesia's national development; with a national resilience approach. From the discussion it was concluded that the National Management Information System needs to be strengthened to support the Acceleration of Indonesia's National Development. Existing obstacles include: a) the absence of regulations and policies that support the integration of data from various government agencies and data privacy; b) Institutions are not yet optimal, causing coordination between agencies to be less focused and a lack of monitoring mechanisms; c) unpreparedness of digital infrastructure and Talent Human Resources to support Simnas accessibility; and the available budget is also inadequate, thus hampering the development and maintenance of Simnas. The efforts made to strengthen support for the acceleration of Indonesia's national development are: a) Synchronization of laws and regulations; b) Professional institutional arrangement and development; c) Accelerate the development of digital infrastructure to make it more adequate so that public services can be improved; administrative processes become more efficient; the government can be more responsive to community needs, increase productivity and national competitiveness; d) Preparing Digital Talent Human Resources, and preparing an adequate budget.